DNA barcoding and inferred genetic diversity of epinephelinae groupers from Peninsular Malaysia using mitochondrial cytochrome c oxidase I gene and microsatellites - Abdul Aziz, Nurnadia Marshita (2017)
This study was conducted with the purpose of validating the species identity and genetic diversity of groupers from Peninsular Malaysia. All samples were collected from across the Peninsular Malaysian waters and stored in ethanol (95%) for short term storage before being placed into -20°C freezer. All steps were done in a sterile environment to avoid any contamination of samples. A total of 131 individuals comprising of 12 species from three genera were collected from coastal areas of Johor (N=4), Kedah (N=12), Kelantan (N=4), Malacca (N=4), Negeri Sembilan (N=2), Pahang (N=14), Perak (N=15), Selangor (N=22) and Terengganu (N=54). All 12 species were identified as Cephalopholis boenak, C. formosa, C. miniata, Epinephelus areolatus, E. bleekeri, E. coioides, E. corallicola, E. erythrurus, E. fuscoguttatus, E. poecilonotus, Plectropomus leopardus and P. maculatus.